Michel Foucault y la biopolítica - Barrera, Jorge Martínez (Sapientia, 2011)
The paper describes the concept of “biopolitics” used by Michel Foucault in his mature writings. “Biopolitics” shows a new pattern of political practice before which the classical terms of virtue ethics or the modern ones of rights are clearly insufficient. A possible new vocabulary is examined based upon the development of the State and the increasing way in which the State considers the body as the very territory of inscription of politics.